Economics and politics of water resources development: Uda Walawe Irrigation Project, Sri Lanka - Molle, Francois; Renwick, M. (International Water Management Institute, 2005)
The Uda Walawe Irrigation and Resettlement Project (UWIRP) located in the Southern dry zone of Sri Lanka was initiated in the early 1950s. The original plan for the UWIRP was a highly ambitious social, economic and physical engineering project aimed at creating a modern, profitable agriculture sector. This report examines the history of water resources development and investment decisions for the UWIRP over a period of 50 years and uncovers underlying processes that shaped the evolution of the project and highlights the limitation of viewing development as a mere set of technical and social engineering endeavors.